2019
DOI: 10.1101/557405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flooding and hydrologic connectivity modulate community assembly in a dynamic river-floodplain ecosystem

Abstract: 29Braided river floodplains are highly dynamic ecosystems, where aquatic communities are 30 strongly regulated by the hydrologic regime. So far, however, understanding of how flow 31 variation influences assembly mechanisms remains limited. 32 We collected benthic chironomids and oligochaetes over a year across a lateral connectivity 33 gradient in the semi-natural Tagliamento River (Italy). Four bankfull flood events occurred 34 during the study, allowing the assessment of how flooding and hydrologic conne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Over evolutionary time scales, many aquatic organisms have adapted advantageous life‐history strategies linked to environmental cues of predictable floods (e.g., changes in discharge, water level, temperature; Lytle & Poff, 2004; Winemiller, 2005; Winemiller & Rose, 1992). However, not all floods are predictable, and frequency of unpredictable floods is expected to increase with climate change (Poff, 2002), requiring additional research to sufficiently characterise ecological responses to atypical floods (Larsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over evolutionary time scales, many aquatic organisms have adapted advantageous life‐history strategies linked to environmental cues of predictable floods (e.g., changes in discharge, water level, temperature; Lytle & Poff, 2004; Winemiller, 2005; Winemiller & Rose, 1992). However, not all floods are predictable, and frequency of unpredictable floods is expected to increase with climate change (Poff, 2002), requiring additional research to sufficiently characterise ecological responses to atypical floods (Larsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wang et al (2020) found that stochastic processes were less pronounced for archaeal than for bacterial communities in a subtropical river‐bay system, and Gad et al (2020) found that deterministic processes were primarily governing the microeukaryotic habitat specialists while stochastic processes were more important for habitat generalists in an anthropogenically impacted river. Changes in hydrological regimes could also influence the relative importance of deterministic and stochastic processes, as stable hydrological periods tend to allow aquatic communities to assemble deterministically (Isabwe et al 2018; Larsen et al 2019).…”
Section: Figmentioning
confidence: 99%
“…However, most of the floodplains are isolated from river mainstream at low flow when most studies are conducted, and the concept of the connectivity is not well defined. In fact, aquatic communities in floodplain waterbodies are not only influenced by the environmental variation that is observed at low flow; they are also strongly influenced by the hydrological and biological processes during flood and flood recession periods (Larsen et al., 2019; Thomaz et al., 2007). For example, flow pulses may differently modify the physical and chemical environment of each waterbody, thereby altering the suitability of habitats for aquatic organisms over time and space (Tockner et al., 2000; Ward et al., 1999).…”
Section: Introductionmentioning
confidence: 99%